Peran mahasiswa KKN UNP dalam Kesenian Randai di Koto Lipek Pageh - Fitra, Halkadri; Firlana, Firlana; Oktavia, Suci; Ihsan, Maulana; Al Arasy, Habib; Ardi, Giffary (Manaruko: Jurnal Pengabdian Masyarakat, 2025)
Randai art is one of the arts in West Sumatra. Koto Lipek Pageh is one of the areas that has this art. Many people are enthusiastic about following and learning this art, from children to adults. This study aims to examine the role of students of the Community ServiceProgram (KKN) of Padang State University (UNP) in actively participating in this art. Field observations and participation in Randai activities show that UNP KKN students have a role in society. Therefore, the KKN program has great potential in maintaining the continuity of traditions, customs, and arts in the midst of social changes that continue to develop